On stability of a nonlinear pendulum - Kengne, E. (Нелінійні коливання, 2003)
Методом Ляпунова знайдено достатню умову стiйкостi руху нелiнiйного маятника. By means of Liapounov’s method, we establish a sufficient condition for stability of a nonlinear pendulum.